If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4y + -5) + -1(3y + 6) = -2(y + 6) Reorder the terms: 2(-5 + 4y) + -1(3y + 6) = -2(y + 6) (-5 * 2 + 4y * 2) + -1(3y + 6) = -2(y + 6) (-10 + 8y) + -1(3y + 6) = -2(y + 6) Reorder the terms: -10 + 8y + -1(6 + 3y) = -2(y + 6) -10 + 8y + (6 * -1 + 3y * -1) = -2(y + 6) -10 + 8y + (-6 + -3y) = -2(y + 6) Reorder the terms: -10 + -6 + 8y + -3y = -2(y + 6) Combine like terms: -10 + -6 = -16 -16 + 8y + -3y = -2(y + 6) Combine like terms: 8y + -3y = 5y -16 + 5y = -2(y + 6) Reorder the terms: -16 + 5y = -2(6 + y) -16 + 5y = (6 * -2 + y * -2) -16 + 5y = (-12 + -2y) Solving -16 + 5y = -12 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -16 + 5y + 2y = -12 + -2y + 2y Combine like terms: 5y + 2y = 7y -16 + 7y = -12 + -2y + 2y Combine like terms: -2y + 2y = 0 -16 + 7y = -12 + 0 -16 + 7y = -12 Add '16' to each side of the equation. -16 + 16 + 7y = -12 + 16 Combine like terms: -16 + 16 = 0 0 + 7y = -12 + 16 7y = -12 + 16 Combine like terms: -12 + 16 = 4 7y = 4 Divide each side by '7'. y = 0.5714285714 Simplifying y = 0.5714285714
| 5(x-4(1-2x)-6)-3(x+10)=40x-12 | | 11x-97=57 | | P=6+18 | | -9=x/4-3 | | 4(y+2)=36+4(6y+12) | | (4y-7w-6)(3y+4)=0 | | Ln(x-2)=2-ln(x-4) | | 16x-24=2x-10 | | -x+156=268 | | (9+w)(5w-8)=0 | | 7e+2=3e+8 | | 21+2x=171 | | 2(x-2)=3x-2 | | 9b+b+8b=(-23) | | 212-v=130 | | x=8037.42-x-.01 | | 2(x-1)=5(x-7) | | x=.014-8037.42 | | (2y+5)(3-y)=0 | | 17-5*3+4= | | 0=(-16t^2)+(48t)+(160) | | 10x-6=10+2x | | (x+2)2=64 | | 12+8y=18 | | 15v^2+11v-12= | | 6x+14y=26 | | -1/2x-2/3=1/7 | | 3(2x+1)=(-39) | | 12x-11=10x-1 | | B^3/4=16 | | f=f(R) | | 2x+12=31-3(x) |